Morphospace of lanternfish larvae and their interplay with oceanographic conditions from the southeastern Pacific Ocean - Orrego, Fernanda S.; Benitez, Hugo A.; Castillo, Manuel I.; Cumplido, Nicolas; Fabres, Alejandra; Figueroa-Gonzalez, Yanara; Morales, Claudia; Zavala-Munoz, Francisca; Landaeta, Mauricio F. (My University, 2024)
Lanternfish larval morphology is highly variable probably due to their adaptations to highly variable environmental conditions throughout ontogeny. To study the morphological variability of the larval stage of lanternfishes, samples were collected from the southeast Pacific Ocean between 2014 and 2022. Of the 24 species, nine belonged to the subfamily Lampanyctinae, two to the subfamily Diaphinae, one to the subfamily Notolychinae, one to the subfamily Gymnoscopelinae and 11 to the subfamily Myctophinae. A principal component analysis indicated the presence of body shapes varying from a slender and curved body, and upper jaw oriented downwards, with relatively rounded eyes, to taxa with robust bodies, particularly both the head and trunk, and elongated eyes in a dorsal-ventral plane (PC1 33%). Also, specimens varied from having short jaw, short snout, and slender body, to specimens with larger jaw (reaching behind the eye) and taller snout and trunk (PC2, 23%). Allometric effects were related to variations in body curvature and thickness (Diaphus theta, 12.9%), the curvature of the body and position of the eyes (Lampanyctodes hectoris, 25.1%), lengthening of the jaw and increase in eye size (Diogenichthys atlanticus, 24.6%), and a narrower body and smaller eyes (Hygophum bruuni, 20.5%). Four of the five subfamilies showed covariation between morphometrics and environmental conditions. Diaphinae, Gymnoscopelinae and Lampanyctinae body shape covaried with mean sea temperature of the water column, while Myctophinae larval shape covaried with mean salinity. In conclusion, this study quantifies shape variations during early lanternfish ontogeny from the southeastern Pacific Ocean, identifying main differences and allometric changes between the subfamilies belonging to Myctophidae, with a covariation between the shape of most lanternfish larvae and the environmental conditions experienced by myctophid early stages.
Keywords: myctophidae; lampanyctinae; myctophinae; oceanography; chile; southeast pacific